Community’s Satisfaction with Maternal Health Services Provided by LHW’s in District Jehlum, Pakistan (Journal of Asian Development Studies, 2013)
Lady Health Workers Program is a significant initiative by Government of Pakistan to improve the health of women in Pakistan. As the medium community Lady Health workers provide services related to maternal health in their own community. The research was based on quantitative research design in which sample of 120 women from the three areas of district Jehlum were selected by using purposive convenient sampling technique. Semi structured Questionnaire was the tools of study. The findings of the study indicated LHWs were providing services related to maternal health for improving women health in district Jehlum. The study concludes that community is satisfied from the maternal services that were being provided by LHWs.